Structural behaviour of reinforced concrete beams containing recycled polyethylene terephthalate and sugarcane bagasse ash - Chukwuemeka Daniel; Richard Ocharo Onchiri; Benard Otieno Omondi (Applications in Engineering Science, 2024)
Concrete is a widely used construction product. This product is presently concerned with the depleting nature of natural sand. Concrete is also being considered with supplementary materials to enhance its footprints. Hence, this study's goal is to examine the performance of reinforced concrete (RC) beams consisting of sustainable materials. The study seeks to qualify the use of concrete made using Sugarcane Bagasse Ash (SCBA) and Recycled Polyethylene Terephthalate (RPET) as structural elements. Proportionately, 10 % RPET is used to partially substitute sand, and 5 % SCBA is used to partially substitute cement. The innovation of this study is in the dual substitution approach and structural behaviour examination. The research probes how RPET and SCBA affect the RC beams’ flexural and shear capacities. The tests are completed ensuing 28 days of water curing. Three RC beams are made for each of the conventional concrete and SCBA-RPET concrete. A set of beams is made for the shear capacity test, while another set is made to examine flexural capacity. The beam dimensions are 160 × 200 × 1200mm3. The findings inform that the beams made with 5 % SCBA and 10 % RPET have a flexural capacity of 11 % less than the conventional beams'. However, the SCBA-RPET beams revealed a shear capacity that is 17.38 % more than the conventional beams'. The crack patterns during and after the shear and flexural strength tests are similar and comparable for the SCBA-RPET beams and the conventional beams. Thus, a sustainable concrete mix suitable for use as a structural beam is derived.